(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the significant role of music in instilling national values in younger generations. It analyzes how Uzbek folk songs, maqom traditions, and traditional instruments express values such as patriotism, compassion, ethics, and diligence. Music is presented not only as a source of aesthetic pleasure but also as a means of cultural memory, historical consciousness, and national identity formation. The study also addresses the role of music in fostering social awareness and moral resilience among youth.